To Serve the Queen, To Serve the Lineage: Kinship Networks and Functions of the Ladies-in-waiting in Violant de Bar’s Household (Edad Media. Revista de Historia, 2026)
This article analyzes the female household of Queen Violant de Bar as a political and relational structure central to late medieval Aragonese monarchy. Using a prosopographical approach, it reconstructs kinship networks, service trajectories, and marriage strategies involving nearly fifty documented ladies and maidens. The study shows how major noble lineages positioned multiple women simultaneously at court, converting household service into a mechanism for social mobility, factional negotiation, and the consolidation of alliances. It also highlights the political agency of these women, whose proximity, mediation, and influence shaped decision-making processes and contributed to the broader governance dynamics of the royal court.
Keywords: Queenship; Networks; Violante of Bar; Crown of Aragon; Ladies-in-Waiting